1962 mha 1976 ʼa tvaṅʻʺ Mranʻ mā bhāsā phraṅʻʹ thutʻ ve so Mranʻ mā nuiṅʻ ṅaṃ reʺ cā ʼupʻ myāʺ cā cu cā raṅʻʺ - Sanʻʺ ʼOṅʻ, Moṅʻ (s.n.], 1978)
Annotated bibliography of books in Burmese language, on history of Burma, published there during the period 1962-1976; thesis for diploma in library science submitted to Rangoon Arts and Science University.